Activity of alkanmonooxygenase alkB gene in strains of hydrocarbon-oxidizing bacteria isolated from petroleum products - T. N. Shapiro; N. A. Manucharova; E. S. Lobakova (Вавиловский журнал генетики и селекции)
Alkanmonooxygenase enzymes AlkB and Cyp153 are responsible for the aerobic degradation of n-alkanes of petroleum and petroleum products. To prove the usage of n-alkanes from oil and petroleum products by hydrocarbon- oxidizing bacteria isolated from aviation kerosene TS-1 and automobile gasoline AI-95, the detection of the key genes alkB, Alk1, Alk2, Alk3 and Cyp153 encoding alkanmonooxygenases AlkB and Cyp153 (responsible for the oxidation of hydrocarbons with a certain chain length) was carried out. It was found that bacterial strains isolated from TS-1 jet fuel, except Deinococcus sp. Bi7, had at least one of the studied n-alkane degradation genes. The strains Sphingobacterium multivorum Bi2; Alcaligenes faecalis Bi3; Rhodococcus sp. Bi4; Sphingobacterium sp. Bi5; Rhodococcus erythropolis Bi6 contained the alkB gene. In the strains of hydrocarbon-oxidizing bacteria isolated from gasoline AI- 95, this alkanmonooxygenase gene was not detected. Using the real-time PCR method, the activity of the alkB gene in all bacterial strains isolated from petroleum products was analyzed and the number of its copies was determined. By real-time PCR using a primer with a different sequence of nucleotides to detect the alkB gene, its activity was established in all bacterial strains isolated from gasoline AI-95; besides, the strain Paenibacillus agaridevorans Bi11 was assigned to the group with a high level of its activity (1290 copies/ml). According to the assessment of the growth of isolated hydrocarbon-oxidizing bacteria on a solid Evans mineral medium with the addition of the model mixture of hydrocarbons, the strains were divided into three groups. The distributions of strains of hydrocarbon-oxidizing bacteria in the groups based on the activity of the alkB gene and groups formed based on the growth ability and use of the model mixture of hydrocarbons and petroleum products were found to be consistent. The results obtained indicate that we need to use a complex of molecular and physiological methods for a comprehensive analysis of the distribution of the studied genes in bacteria and to assess their activity in the strains of hydrocarbon-oxidizing bacteria capable of biodegradation of petroleum hydrocarbons.